MEASURING AND COMPENSATING FOR OFF-LINE TO RUNNING MACHINERY MOVEMENT - Tuan, Phan Anh; Abidin, Zainal; Bagiasna, Komang (Mesin, 2005)
Actually, all rotating equipments which connected one to each other undergo a change in position during start-up (off-line) and this condition will affect the alignment of the shafts while running. The off-line to running movement characteristics of the vast majority of rotating machinery in industries have never been measured. It is very important to know how much movement occurred before concluding that it is insignificant and can be ignored. This paper will show the characteristics of both cold and hot misalignment. The purpose of this work is to analyze the influence of temperature to misalignment of rotating equipments that has been mentioned in some references but never been investigated. The objective of this work is to find out the characteristics of hot misalignment and to compensate for Off-Line to Running (OL2R) machinery movement. The results of the experiments and analysis show that the misalignment condition changes during operation and it strongly influences on the vibration level of the rotating machinery. In this case, the smaller the misalignment value, the smaller vibration level of the rotating machinery.